3D Virtual Simulation Software For Underwater Application. - Mohd Hamzah, Mohd Salzahrin; Zakaria, Muzammer; Abd Jalil, Mohd Fazli Izwan; Zamli, Kamal Zuhairi (2008)

(untitled)
This paper shows the use of 3D virtual simulation, representing the actual object movement underwater.